EVALUASI PERATURAN DAERAH NOMOR 6 TAHUN 2015 MENGENAI PENGENDALIAN MENARA TELEKOMUNIKASI DI KOTA PEKANBARU TAHUN 2020 - Muhammad Zaki; Wan Asrida (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
Telecommunications Tower is a technological development that becomes a necessity for the community that cannot be separated from communication tools, so that there is an increase in development. In Regional Regulation No. 6 of 2015 concerning the arrangement and control of telecommunications towers in Article 8, it is known that the control of telecommunications towers includes: 1. Control of the construction of telecommunication towers. 2. Control of the operation of telecommunications towers. Several towers in Pekanbaru City are still under construction that are not in accordance with the telecommunication tower construction zone. It is very dangerous for buildings around the tower. In controlling the operation of the tower there are security, safety, and architecture. Meanwhile, in Pekanbaru City, there are several towers whose management control is not in accordance with Perda No. 6 of 2015. The purpose of this study is to describe the evaluation of regional regulation number 6 of 2015 in controlling the construction of telecommunication towers and controlling the operation of telecommunication towers. The theoretical concept used is the CIPP model evaluation theory (Context, Input, Process, and Product) by Daniel Stufflebeam. This type of research is descriptive qualitative. Data collection techniques were carried out by interviews and documentation. The results of this study are that in controlling the operation of this telecommunications tower, it is not in accordance with existing regulations, for example there are still towers that should be forcibly demolished, in fact there are still standing firmly close to the surrounding buildings, whether human resources are still lacking knowledge towards the construction of telecommunication towers where security and safety should be the main thing that must be done. Keywords: Control, Telecommunication Tower, Evaluation